Chirped pulse spectrally resolved interferometry without the direction ambiguity and the dead zone. (May 2022) - Wang, Jing; Lu, Yang; Sun, Xiongxin; Zhao, Huining; Jin, Xueying; Gao, Haoran; Yu, Liandong
Highlights: The direction ambiguity and the dead zone in spectrally resolved interferometry can be eliminated by shaping and f r -scanning the femtosecond pulse trains. By stretching the measurement pulse, a derivative trend is generated to identify the direction using an unequal-path Mach-Zehnder fiber structure. A controllable optical path difference is introduced by accurately tuning the pulse repetition rate to fill the dead zone. The measurement range of chirped pulse spectrally resolved interferometry can be extended to more than twice. Abstract: In this investigation, a simple method is proposed to extend the measurement range of spectrally resolved interferometry, which is limited by the direction ambiguity and the dead zone. By stretching the measurement pulse, a derivative trend is generated to identify the direction using an unequal-path Mach–Zehnder fiber structure. Besides, the dead zone is eliminated by introducing a controllable optical path difference. The experimental results confirme that the full measurement range can be extend to more than twice.